Dissecting Inter-domain Cooperativity in the Folding of a Multi Domain Protein. Issue 18 (3rd September 2021) - Laursen, Louise; Gianni, Stefano; Jemth, Per
Graphical abstract: Highlights: Data on multi-domain protein folding is scarce. The three-domain supramodule PDZ3-SH3-GK (PSG) displays two folding units. SH3-GK folds cooperatively and slower than PDZ3. PDZ3 traps an SH3-GK intermediate during concurrent refolding of all three domains. Protein domains are not necessarily the minimal folding unit. Abstract: Correct protein folding underlies all cellular functions. While there are detailed descriptions and a good understanding of protein folding pathways for single globular domains there is a paucity of quantitative data regarding folding of multidomain proteins. We have here investigated the folding of a three-domain supramodule from the protein PSD-95, consisting of one PDZ domain, one SH3 domain and one guanylate kinase-like (GK) domain. This supramodule has previously been shown to work as one functional unit with regard to ligand binding. We used equilibrium and kinetic folding experiments to demonstrate that the PDZ domain folds faster and independently from the SH3-GK tandem, which folds as one cooperative unit. However, concurrent folding of the PDZ domain slows down folding of SH3-GK by non-native interactions, resulting in an off-pathway folding intermediate. Our data contribute to an emerging description of multidomain protein folding in which individual domains cannot a priori be viewed as separate folding units.